Bridging multisensory and ud towards compassionate design in Malaysia interior design industry (ARTEKS : Jurnal Teknik Arsitektur, 2025)
In the field of interior design, creating inclusive and engaging spaces is crucial. Universal Design (UD) and multisensory are supportive approaches that can work together to achieve this, however there is a lack of studies on the importance of universal design within the Malaysian interior design industry and its relationship with multisensory in buildings. UD emphasizes building environments that are practical and accessible to everyone, while multisensory highlights the significance of engaging all senses according to the principles of sensory design. Hence, the impact of multisensory on universal design in creating inclusive and accessible interior design will be discussed in this research. While compassionate design practices mediate the relationship between the principles of universal design and the principles of sensory design, this study has two objectives: To identify the necessity of implementing universal design in different types of buildings; and, to investigate the interaction between multisensory and universal design to promote compassionate design practices. Data was gathered through questionnaires given to people in the built environment industry. It is expected that different types of buildings have varying priorities for sensory aspects, and the integration of UD and multisensory design is both important and impactful.
Keywords: Accessibility; Inclusivity; Interior design; Multisensory; Universal design